2008
DOI: 10.18637/jss.v024.i03
|View full text |Cite
|
Sign up to set email alerts
|

ergm: A Package to Fit, Simulate and Diagnose Exponential-Family Models for Networks

Abstract: We describe some of the capabilities of the ergm package and the statistical theory underlying it. This package contains tools for accomplishing three important, and interrelated, tasks involving exponential-family random graph models (ERGMs): estimation, simulation, and goodness of fit. More precisely, ergm has the capability of approximating a maximum likelihood estimator for an ERGM given a network data set; simulating new network data sets from a fitted ERGM using Markov chain Monte Carlo; and assessing ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
757
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 863 publications
(767 citation statements)
references
References 35 publications
2
757
0
8
Order By: Relevance
“…A large set of local structures are provided in the literature to use with exponential random graph models (Hunter et al, 2009). Two previous studies (Simpson et al, , 2012 .…”
Section: Local Structure Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large set of local structures are provided in the literature to use with exponential random graph models (Hunter et al, 2009). Two previous studies (Simpson et al, , 2012 .…”
Section: Local Structure Definitionsmentioning
confidence: 99%
“…We then compared the observed network with the simulated network based on three global descriptive network characteristics: degree (connectivity), geodic distance (shortest path) and edge-wise shared partners (clustering) from the Bergm package (Caimo and Friel, 2014). Additionally, we implemented the triad census (i.e., subset of motifs), that determines the contributions, as a probability, of one, two or three connections between all possible node triples (Hunter et al, 2009;Morris et al, 2008), and compared these contributions between the observed and simulated networks.…”
Section: Goodness-of-fitmentioning
confidence: 99%
“…For details about interpreting the output above, see similar models in other articles in this journal volume -e.g., model3 in Hunter et al (2008b) or model2 in Goodreau et al (2008a) -and read the descriptions of the edges and nodematch terms below.…”
Section: Terms Used In Exponential-family Random Graph Modelsmentioning
confidence: 99%
“…These terms are used in calls to the ergm function, to fit an ergm model; calls to simulate, to simulate networks from an ergm model fit; and calls to summary, to obtain measurements of network statistics on a dataset. See Hunter et al (2008b) and Goodreau, Handcock, Hunter, Butts, and Morris (2008a) for examples of these functions. The terms described below are also available to the other packages in the statnet suite.…”
Section: Introductionmentioning
confidence: 99%
“…that enable the fitting of ERGMs (see Table 1). Basic ERGMs, including for bipartite 236 networks, can be fitted using the package ergm Hunter et al, 2008). 237 We provide an example demonstrating the model output, convergence diagnostics and These diverse applications demonstrate that ERGMs can be used to model affiliative 294 and antagonistic networks, to analyse differences within and among-populations, and to 295 understand dyadic and whole network-level processes.…”
mentioning
confidence: 99%